Comparative Mitogenomic Analysis Reveals Dynamics of Intron Within and Between Tricholoma Species and Phylogeny of Basidiomycota - Huang, Wenli; Feng, Huiyu; Tu, Wenying; Xiong, Chuan; Jin, Xin; Li, Ping; Wang, Xu; Li, Qiang (Frontiers in Genetics, 2021)
The genus of Tricholoma is a group of important ectomycorrhizal fungi. The overlapping of morphological characteristics often leads to the confusion of Tricholoma species classification. In this study, the mitogenomes of five Tricholoma species were sequenced based on the next-generation sequencing technology, including T. matsutake SCYJ1, T. bakamatsutake, T. terreum, T. flavovirens, and T. saponaceum. These five mitogenomes were all composed of circular DNA molecules, with sizes ranging from 49,480 bp to 103,090 bp. Intergenic sequences were considered to be the main factor contributing to size variations of Tricholoma mitogenomes. Comparative mitogenomic analysis showed that the introns of the Agaricales mitogenome experienced frequent loss/gain events. In addition, potential gene transfer was detected between the mitochondrial and nuclear genomes of the five species of Tricholoma. Evolutionary analysis showed that the rps3 gene of the Tricholoma species was under positive selection or relaxed selection in the evolutionary process. In addition, large-scale gene rearrangements were detected between some Tricholoma species. Phylogenetic analysis using the Bayesian inference and maximum likelihood methods based on a combined mitochondrial gene set yielded identical and well-supported tree topologies. This study promoted the understanding of the genetics, evolution, and phylogeny of the Tricholoma genus and related species.